Exploring the heterogenous impacts of environmental taxes on environmental footprints: An empirical assessment from developed economies - Rafique, Muhammad Zahid; Fareed, Zeeshan; Ferraz, Diogo [UNESP]; Ikram, Majid; Huang, Shaoan (Elsevier, 2022)
The Organization for Economic Co-operation and Development (OECD) economies face the challenges of rising energy demand, urbanization, and growing environmental issues (rising ecological footprint and less biodiversity). The primary objective of this article is to explore the role of environmental taxes and economic growth on the growing ecological footprint in 29 OECD economies. The autoregressive distributed lag (ARDL) approach and the related intermediate estimators are used to attain the purpose. The two substitute single equation estimators, DOLS, FMOLS, and fixed effect, are also employed to check the robustness of the ARDL estimator. Empirical results reveal that environmental-related taxes, economic growth, foreign direct investment, energy use, urbanization, renewable energy, and industrialization significantly influence the long-term ecological footprint in OECD countries. The dynamics of the studied variables got changed when time is considered. In the short-term, these dynamics are mixed while staying similar in the long-term across the OECD countries. This is attributed to varying levels of renewable energy use and industrialization progress in OECD countries. The empirical conclusions suggest that OECD economies need careful monitoring of environmental regulations for energy usage policies and cleaner production goals.
Keywords: Ecological footprint; Economic growth; Environmental related taxes; OECD countries; Westerlund cointegration